Self‐compatibility is over‐represented on islands. Issue 1 (6th April 2017) - Grossenbacher, Dena L.; Brandvain, Yaniv; Auld, Josh R.; Burd, Martin; Cheptou, Pierre‐Olivier; Conner, Jeffrey K.; Grant, Alannie G.; Hovick, Stephen M.; Pannell, John R.; Pauw, Anton; Petanidou, Theodora; Randle, April M.; et al.
Summary: Because establishing a new population often depends critically on finding mates, individuals capable of uniparental reproduction may have a colonization advantage. Accordingly, there should be an over‐representation of colonizing species in which individuals can reproduce without a mate, particularly in isolated locales such as oceanic islands. Despite the intuitive appeal of this colonization filter hypothesis (known as Baker's law), more than six decades of analyses have yielded mixed findings. We assembled a dataset of island and mainland plant breeding systems, focusing on the presence or absence of self‐incompatibility. Because this trait enforces outcrossing and is unlikely to re‐evolve on short timescales if it is lost, breeding system is especially likely to reflect the colonization filter. We found significantly more self‐compatible species on islands than mainlands across a sample of > 1500 species from three widely distributed flowering plant families (Asteraceae, Brassicaceae and Solanaceae). Overall, 66% of island species were self‐compatible, compared with 41% of mainland species. Our results demonstrate that the presence or absence of self‐incompatibility has strong explanatory power for plant geographical patterns. Island floras around the world thus reflect the role of a key reproductive trait in filtering potential colonizing species in these three plant families.